Social Justice Innovation in Africa. - Engström, Viljam; Mustaniemi-Laakso, Maija; Stark, Laura (Oxford : Taylor & Francis Group, 2024)
Adopting a multidisciplinary approach, this book discusses the potential of social innovation in the pursuit of social justice in Africa. This book will be of interest for researchers and policy makers across the fields of human rights, economics, business, development studies, anthropology, and African studies.
Cover -- Half Title -- Endorsements Page -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- List of Contributors -- Preface -- Acknowledgements -- Introduction: Understanding Social Innovation in Africa -- Part I: Conceptualising Social Justice Innovation -- 1 Social Justice Innovation: A Cross-Disciplinary and Multilayered Agenda -- 2 Contextualizing and Conceptualizing the Social Enterprise: The Cooperative as an Enabler of Social justice in Sub-Saharan Africa -- Part II: Social Entrepreneurship -- 3 From Coffins to Coins: Ethiopian "iddir" Navigating the Frontier of Social Enterprise -- 4 'Baron/Baroness' Food-Get-Together Celebrations and Mukando Village Contributions as Tools for Entrepreneurial Socialization and Innovation in Chikonye, Maheya, and Murairwa Villages in Rural Zimbabwe -- 5 Self-Organized Waste Pickers: Marginalized Yet Vital to the African City of Bamako -- 6 Surviving on the Margins of Legality: Familial Ties, the Informal Economy, and Re-Imagining Social Protection in Kenya -- Part III: Social Technologies -- 7 Livelihood Outcomes of Social Innovations for Mobile Agricultural Extension Service Delivery in South-Central Uganda -- 8 Enhancing Social Justice? Experimenting with Social Media in Preservice Teacher Education at Makerere University in Uganda -- Part IV: Societal Practices -- 9 The Constitutional Court of South Africa as an Agent of Social Justice -- 10 Community Perceptions of Social Justice in Benefit Distribution Mechanisms of Forestry Carbon Projects in Uganda -- 11 Leveraging and Regulating Pension Funds for Sustainable Development and Socially Responsive Investments in the Namibian Economy -- 12 Law, Clinics, and Social Innovation in Africa: Addressing Justice Gaps -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books